Why True Believers Make the Ultimate Sacrifice: Sacred Values, Moral Convictions, or Identity Fusion? - Martel, Francois Alexi; Buhrmester, Michael; Gómez, Angel; Vázquez, Alexandra; Swann, William B. (Frontiers in Psychology, 2021)
Recent research has identified three promising candidates for predicting extreme behavior: sacred values, moral convictions, and identity fusion. Each construct is thought to motivate extreme behavior in unique ways: sacred values trigger extreme actions when people are asked to compromise cause-related values for personal gain; moral convictions trigger extreme actions when a cause is aligned with one’s moral compass; and identity fusion triggers extreme actions when a cause is inextricably associated (“fused”) with the personal-self. In six studies, we asked which of the three constructs (either alone or in combination) was most predictive of sacrifice for a cause. We measured all three constructs with respect to either of two causes: gun rights (Studies 1-3) or abortion rights (4-6). The outcome measure was endorsement of fighting and dying for the cause. Although all three constructs were significant predictors of the outcome measure when considered separately, identity fusion consistently emerged as the strongest predictor of endorsement of self-sacrifice when all three were considered simultaneously. This pattern occurred regardless of the target cause (gun or abortion rights), the participant’s position on the cause (i.e., pro-gun or anti-gun, pro-choice or pro-life), or nationality (American vs. Spanish). Also, there was no evidence that the predictors interacted to predict the outcome measure. Finally, a manipulation that threatened the validity of the personal-self strengthened the relationship between endorsement of self-sacrifice and both (a) identity fusion and (b) moral convictions. The latter finding suggests that threats to the validity of one’s self-views may amplify the extreme behaviors of true believers.